2018
DOI: 10.1111/jce.13785
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of edema after cryo and radiofrequency ablations based on serial magnetic resonance imaging

Abstract: Introduction: Radiofrequency (RF) and cryoablation are routinely used to treat arrhythmias, but the extent and time course of edema associated with the two different modalities is unknown. Our goal was to follow the lesion maturation and edema formation after RF and cryoablation using serial magnetic resonance imaging (MRI).Methods and Results: Ventricular ablation was performed in a canine model (n = 11) using a cryo or an irrigated RF catheter. T2-weighted (T2w) edema imaging and late gadolinium enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 20 publications
2
28
0
2
Order By: Relevance
“…The use of MRI for evaluating myocardial substrate as well as lesion quality assessment is becoming more routine. [6][7][8][9]11,[16][17][18] In this study, we confirmed that that acute LGE-MRI overestimates chronic lesion size by almost a factor of three and that the chronic LGE-MRI is an excellent predictor of pathology-determined lesion size both in terms of depth and volume.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The use of MRI for evaluating myocardial substrate as well as lesion quality assessment is becoming more routine. [6][7][8][9]11,[16][17][18] In this study, we confirmed that that acute LGE-MRI overestimates chronic lesion size by almost a factor of three and that the chronic LGE-MRI is an excellent predictor of pathology-determined lesion size both in terms of depth and volume.…”
Section: Discussionsupporting
confidence: 80%
“…In that study, no CF data was shown for Cryo ablation as CF has little relevance for Cryo lesions. 9) On the other hand, higher CF is related to larger lesion size in RF ablation but there have been no data to date on how to make a durable scar while minimizing the acute edema relative to the lesion size. 10) The main results obtained from this study are as follows: The primary predictor of ventricular lesions with relatively larger edema was the relatively smaller CF and FTI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their paper, they showed that acute edema by cryoablation was significantly smaller than that by RFA. 11) The relationship between the atrial edema and AF recurrence might be less in CBA compared with RFA. Further evidence is needed to clarify this point.…”
Section: Article P618mentioning
confidence: 99%